Tumor pH-Responsive Nanocarriers With Light-Activatable Drug Release for Chemo-Photodynamic Therapy of Breast Cancer - Zhang, Zhang; Gao, An; Sun, Chunyang (Frontiers in Chemistry, 2022)
Developing the bioresponsive nanocarriers with particular tumor cell targeting and on-demand payload release has remained a great challenge for combined chemo-photodynamic therapy (PDT). In this study, an intelligent nanocarrier (DATAT-NPCe6) responded to hierarchical endogenous tumor pH and exogenous red light was developed through a simple mixed micelle approach. The outside TAT ligand was masked to prevent the unexpected interaction in blood circulation. Following the accumulation of DATAT-NPCe6 in tumor tissues, tumor acidity at pH ~6.5 recovered its targeting ability via triggering DA moiety degradation. Furthermore, the cascaded chemo-PDT was accomplished through light-stimulated nanocarriers disassembly and doxorubicin release. Taking the advantage of stability and controllability, this work provides a facile approach to designing bioresponsive nanocarriers and represents a proof-of-concept combinatorial chemo-PDT treatment.